Per il testo degli Scriptores Historiae Augustae - Lucarini, Carlo M. (Hyperboreus, 2014)
The aim of this paper is to cast new light on the textual constitution of some passages of the Historia Augusta. 127 pieces are discussed and for the most of them a new solution is proposed; in the other cases the author argues for a solution already proposed, but not accepted by the editors.